2023
DOI: 10.14202/vetworld.2023.779-785
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of five conjunctival cytology sampling methods in normal cat eyes

Abstract: Background and Aim: Ophthalmological cytology is an easy, informative, rapid, and commonly-used low-cost diagnostic method, but sample collection and preparation are essential steps in obtaining qualitative material for cytological evaluation. This study aimed to evaluate cytological smear quality and animal discomfort after single or three serial conjunctival scrapings in normal cat eyes using five sampling methods. Materials and Methods: Five cytology methods (mini brush, cotton swab, soft brush, Kimura spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Ocular impression cytology is considered a valid diagnostic tool in ophthalmology. Collection with a spatula is not recommended as it produces low-quality samples containing few intact cells, while the mini-brush method is considered the best method, causing no discomfort and yielding a high-quality sample with a sufficient quantity of cells for analysis (Kovalcuka, Sarpio, and Nikolajenko, 2023). Bron et al (2017) reported that in humans, conjunctival goblet cells play an important role in mucin production, which, upon contact with water, forms a mucous layer that constitutes the innermost part of the lacrimal film.…”
Section: Introductionmentioning
confidence: 99%
“…Ocular impression cytology is considered a valid diagnostic tool in ophthalmology. Collection with a spatula is not recommended as it produces low-quality samples containing few intact cells, while the mini-brush method is considered the best method, causing no discomfort and yielding a high-quality sample with a sufficient quantity of cells for analysis (Kovalcuka, Sarpio, and Nikolajenko, 2023). Bron et al (2017) reported that in humans, conjunctival goblet cells play an important role in mucin production, which, upon contact with water, forms a mucous layer that constitutes the innermost part of the lacrimal film.…”
Section: Introductionmentioning
confidence: 99%